До оптимального проектування коліс рухомого складу залізниць при технологічних та експлуатаційних навантаженнях - Резниченко, М. К.; Щепкін, Олександр Віталійович (НТУ "ХПІ", 2005)
The systematic numerical research of railroad car wheel were made using technological heating by induction-heating devices which allowed the establishment of the laws of the stress-strain state of the wheel set elements, during its thermal assembly
Keywords: залізничний транспорт; бандаж; температура нагрівання; залізничне колесо